RESILIENSI PEKERJA HARIAN DIMASA PANDEMI COVID-19 - Dominggus Palmarius; Debi Angelina Br Barus (Empowerment Jurnal Mahasiswa Psikologi Universitas Buana Perjuangan Karawang, 2021)
This study aims to describe of the resilience of daily workers in Maumere city during the covid-19 pandemic. The population in this study were daily workers in the city of Maumere, with purposive sampling technique as a sampling technique. The data collection method used a modified Likert scale, with a validity value range between 0.27-0.66 and a reliability value of 0.848. The results of this study indicate that the resilience of daily workers in the city of Maumere is low with a percentage of 58.6% or as many as 34 daily workers who low with a percentage of 58.6% or as many as 34 daily workers who have low resilience. Penelitian ini bertujuan untuk melihat gambaran resilensi pekerja harian di Kota Muamere dimasa pandemi Covid-19. Populasi dalam penelitian ini adalah pekerja harian yang berada di Kota Maumere, dengan teknik puposive sampling sebagai teknik pengambilan sampel. Metode pengumpulan data dengan menggunakan skala likert modifikasi, dengan rentang nilai validitas antara 0.27-0.66 dan nilai reliabilitas sebesar 0.848. hasil penelitian ini menunjukan bahwa reseliensi pekerja harian di kota Maumere tergolong rendah dengan presentase sebesar 58.6% atau sebanyak 34 orang pekerja harian yang memiliki resilensi rendah.